Meneropong Work-Life Balance selama Covid-19: Studi Kasus Aparatur Sipil Negara di Jakarta Pusat - Edwin Gideon Tongam; Muhammad Fazry Eggy Linardy; Muhammad Kurniawan Saputra; Nopriadi Saputra (Studi Ilmu Manajemen dan Organisasi, 2021)
Purpose: The purpose of this study is to describe and analyze: (1) How the Work-Life Balance, Flexible Working Arrangement, and Telework Ability of the State Civil Apparatus (ASN) in Central Jakarta during the COVID-19 pandemic (2) Measure the effect of Flexible Working Arrangement and Telework Ability on Work-Life Balance (3) Effect of Flexible Working Arrangement on Telework Ability of ASN in Central Jakarta during the COVID-19 pandemic. Research Methodology: The method in this research is quantitative. The research instrument used an online questionnaire distributed to ASN in Central Jakarta in a Google Form. The data analysis method used is a descriptive analysis of variables and respondents, the respondents in this study work in government offices located in the Central Jakarta area. The test used in this research is the Statistical Test and Hypothesis Testing Using the SPSS 25 Application. The sampling technique used is non-probability sampling and uses a convenience and snowball approach with the Krejcie formula. Results: The results of this study indicate that the application of Flexible Working Arrangement and Telework Ability of ASN has a positive effect on their Work-Life Balance. Limitation: The limitation of the research is in the pandemic conditions, which limit researchers from conducting offline research. Contribution: It is hoped that this research can be useful for Government Agencies in the Central Jakarta area as well as a reference for further research on Flexible Working Arrangements, Telework Ability, and Work-Life Balance.